Potensi Pengembangan Ruang Terbuka Hijau (RTH) Publik Aktif di Kota Selong - Lalu Rifky Fadhlurrachman; Muhamad Husni Idris; Evy Aryanti (Jurnal Ilmiah Global Education, 2026)
Law No. 26 of 2007 mandates that the provision of urban public Green Open Space (GOS) must constitute at least 20% of the total urban area within a regency. As Selong City serves as the capital district of East Lombok Regency, it is required to provide adequate facilities and infrastructure, including active public GOS. Currently, the public GOS in Selong City covers 76.716 hectares, accounting for only 2.42% of its total area of 3,168 hectares.The objectives of this study are: (1) to analyze the existing conditions of active public GOS in Selong City; (2) to analyze the criteria for determining potential locations for active public GOS; and (3) to identify potential locations for active public GOS in Selong City. The methodology employed integrates stakeholder analysis, the Delphi method, Analytical Hierarchy Process (AHP), and weighted overlay analysis using Geographic Information Systems (GIS). The results indicate that the requirement for active public GOS in Selong City is 634 hectares. The criteria utilized for site selection include: (1) distribution of existing GOS, (2) land use, (3) population density, (4) land slope, (5) accessibility, (6) supporting facilities, (7) land value zones, and (8) land tenure. The analysis identifies 664 hectares of potential land for active public GOS development, representing 21% of the city's total area. This potential area is categorized into a "highly suitable" zone of 37 hectares and a "moderately suitable" zone of 627 hectares.